2012
DOI: 10.1111/joor.12013
|View full text |Cite
|
Sign up to set email alerts
|

Alexithymic and somatisation scores in patients with temporomandibular pain disorder correlate with deficits in facial emotion recognition

Abstract: Current studies suggest dysfunctional emotional processing as a key factor in the aetiology of temporomandibular disorder (TMD). Investigating facial emotion recognition (FER) may offer an elegant and reliable way to study emotional processing in patients with TMD. Twenty patients with TMD and the same number of age-, sex- and education-matched controls were measured with the Facially Expressed Emotion Labelling (FEEL) test, the 26-item Toronto Alexithymia Scale (TAS-26), the Screening for Somatoform Symptoms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 65 publications
1
25
0
1
Order By: Relevance
“…When facets of alexithymia were considered, 10% of pain was predicted by DIF, DDF and age; 38% of poor health was predicted by DIF and age; finally, 13% of social difficulty was predicted by DIF. These results are line with recent findings highlighting facial emotion recognition deficits in patients with TMD (21).…”
Section: Discussionsupporting
confidence: 93%
“…When facets of alexithymia were considered, 10% of pain was predicted by DIF, DDF and age; 38% of poor health was predicted by DIF and age; finally, 13% of social difficulty was predicted by DIF. These results are line with recent findings highlighting facial emotion recognition deficits in patients with TMD (21).…”
Section: Discussionsupporting
confidence: 93%
“…The data employed for the analysis consisted of 3 consecutive measurements of the PPT at the 2 locations taken at 30‐second intervals, using the mean of these measurements. Chesterton et al (2007) showed that the reliability of pressure algometry is high (intraclass correlation coefficient [ICC], 0.91; 95% confidence interval [CI] 0.82‐0.97) …”
Section: Methodsmentioning
confidence: 99%
“…Brain representation training‐based interventions such as MI, AO and VMF have been proposed as novel therapeutic tools to facilitate motor cortex activity, with or without the actual exercise, for patients who are unable to perform the movements . In this regard, this type of intervention could have a favourable effect on patients with temporomandibular disorders and those with dysphagia in whom pain sensitivity, tongue weakness or motor and emotional processing could be disrupted and related to the maintenance and appearance of the pathologic condition . The combination of motor control exercises and MI has also shown statistically significant changes in sensorimotor function variables of the craniocervical region and in the subjective perception of fatigue, when compared with exercises performed in isolation .…”
Section: Introductionmentioning
confidence: 99%
“…21,22 The ability to recognize faces and facial expressions and participate directly, is required for a perfect intercommunicative relationship. 23 Research studies have shown that diminished quality and quantity of facial expression is associated with chronic face pain, temporomandibular dysfunction, facial asymmetries, and neurological disorders, such as facial paresis and Parkinson's disease; however, it can also be influenced by affective dysfunctions such as depression. 13,24,25 To understand one's own feelings and display them is closely connected with the ability to recognize and interpret them through mimicry and gestures to other human beings.…”
Section: Recognition Of Emotion and Expressionmentioning
confidence: 99%
“…13,24,25 To understand one's own feelings and display them is closely connected with the ability to recognize and interpret them through mimicry and gestures to other human beings. 23,26 When a person recognizes an emotion in another's face, it stimulates a response to mimic the facial expression with their own facial muscles; this has been called the facial reflex. (Fig.…”
Section: Recognition Of Emotion and Expressionmentioning
confidence: 99%